What is Pioneer Positive Deviance—and why is it so effective? - Habermann, Birgit; Worku, Tigist; Gichuki, Leah (International Livestock Research Institute, 2025)
Adaptation pioneers implement uncommon practices and succeed where others fail. This understanding of behavioral adaptation is rooted in the concept of positive deviance. In our research, positive deviants are referred to as adaptation pioneer families or households, encompassing men, women, youth, and the elderly. By studying these uncommon practices, we can support pioneers in sharing their unique approaches with others, fostering social learning for more resilient farming systems.